2009
DOI: 10.1515/cclm.2009.216
|View full text |Cite
|
Sign up to set email alerts
|

Unstimulated high sensitive thyroglobulin measurement predicts outcome of differentiated thyroid carcinoma

Abstract: Background: Thyroglobulin (Tg) measurement following thyrotropin (TSH) stimulation is used in the follow-up of patients with differentiated thyroid carcinoma (DTC). However, high-sensitive assays allow accurate measurement of serum Tg even without TSH stimulation. Here, we prospectively evaluated the impact of unstimulated high-sensitive Tg measurement in early and long-term outcome of patients with DTC. Methods: One hundred and ninety five patients affected with DTC were evaluated. Six months after thyroid ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 15 publications
(15 reference statements)
1
17
0
1
Order By: Relevance
“…However, over the last decade, Tg2G assays that present an FS tenfold greater, in the order of 0.05-0.1 ng/ml, have been developed and validated, and these assays are now routinely used in laboratories worldwide [12,13,14,15,16,17,18,19,20,21]. These studies have shown that when a second-generation assay is employed for Tg measurement, undetectable serum b-Tg has the same predictive value as s-Tg.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, over the last decade, Tg2G assays that present an FS tenfold greater, in the order of 0.05-0.1 ng/ml, have been developed and validated, and these assays are now routinely used in laboratories worldwide [12,13,14,15,16,17,18,19,20,21]. These studies have shown that when a second-generation assay is employed for Tg measurement, undetectable serum b-Tg has the same predictive value as s-Tg.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of these studies analyzed a total of 953 patients, mainly belonging to the group of patients with a low risk of recurrence, using Tg2G assays (0.1 or 0.2 ng/ml), and only 19 of the 953 patients showed evidence of recurrent disease (16 of them seen on neck US). The authors concluded that these patients with undetectable b-Tg rarely have s-Tg greater than 1.0 or 2.0 ng/ml (1.7%) and that they rarely present with metastasis (1.3%) [12,13,14,15,16,17,18,19,20,21]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Некоторые авторы пишут об отсут-ствии необходимости измерения стимулированного ТГ, так как, по их данным, неопределяемый базаль-ный ТГ (<0,1 нг/мл) дает необходимую информацию [82][83]. В клинической практике при базальном уровне ТГ <0,1 нг/мл и отсутствии остаточной ткани ЩЖ по данным УЗИ шеи пациенты могут быть от-несены к группе с ремиссией заболевания.…”
Section: наблюдение пациентов с папиллярными микрокарциномамиunclassified
“…Recently, new methods for serum Tg measurement with functional sensitivity below 0.1 ng/ml became available. Using these assays some authors reported that an undetectable basal serum Tg (<0.1 ng/ml) may give the same information of a stimulated serum Tg value, thus avoiding the need for Tg stimulation (13)(14)(15)(16)(17)(18)(19)(20). However, the higher negative predictive value (NPV) of these tests is at the expenses of a very low specificity and positive predictive value (PPV) and the risk is to expose large numbers of patients, probably free of disease, to extensive testing and/or unnecessary treatment.…”
Section: Follow-up Short Term Follow-upmentioning
confidence: 99%